Reelin controls position of autonomic neurons in the spinal cord - Yip, Joseph W. (The National Academy of Sciences, 2000)
Mutation of the reeler gene (Reln) disrupts neuronal migration in several brain regions and gives rise to functional deficits such as ataxic gait and trembling in the reeler mutant mouse. Thus, the Reln product, reelin, is thought to control cell–cell interactions critical for cell positioning in the brain. Although an abundance of reelin transcript is found in the embryonic spinal cord [Ikeda, Y. & Terashima, T. (1997) Dev. Dyn. 210, 157–172; Schiffmann, S. N., Bernier, B. & Goffinet, A. M. (1997) Eur. J. Neurosci. 9, 1055–1071], it is generally thought that neuronal migration in the spinal cord is not affected by reelin. Here, however, we show that migration of sympathetic preganglionic neurons in the spinal cord is affected by reelin. This study thus indicates that reelin affects neuronal migration outside of the brain. Moreover, the relationship between reelin and migrating preganglionic neurons suggests that reelin acts as a barrier to neuronal migration.